1996
DOI: 10.1073/pnas.93.9.3926
|View full text |Cite
|
Sign up to set email alerts
|

Long-time quantum simulation of the primary charge separation in bacterial photosynthesis.

Abstract: (7)(8)(9)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 38 publications
(45 reference statements)
7
84
1
Order By: Relevance
“…For comparison, we adopt the same electronic parameters used in Ref. 94 and the same system-bath coupling used above,Ĥ el−ph = i=S 1 ,CT,T T |i k,i c k,i q k,i i|. Again the baths have an Ohmic spectral density with Lorentzian cutoff parametrized by λ = 25 meV, Ω = 150 meV, and T = 300 K. We wish to strongly emphasize that although this Hamiltonian (electronic parameters to follow) was originally parametrized based on photosynthetic protein data, the magnitude of the parameters is almost identical with those expected of singlet fission.…”
Section: A Results For Population Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, we adopt the same electronic parameters used in Ref. 94 and the same system-bath coupling used above,Ĥ el−ph = i=S 1 ,CT,T T |i k,i c k,i q k,i i|. Again the baths have an Ohmic spectral density with Lorentzian cutoff parametrized by λ = 25 meV, Ω = 150 meV, and T = 300 K. We wish to strongly emphasize that although this Hamiltonian (electronic parameters to follow) was originally parametrized based on photosynthetic protein data, the magnitude of the parameters is almost identical with those expected of singlet fission.…”
Section: A Results For Population Dynamicsmentioning
confidence: 99%
“…Over 15 years ago, Makri and coworkers performed numerically exact path integral simulations of a three-state model very similar to the one considered here and detailed the dynamical features of two previously proposed, but physically distinct transport mechanisms. 94,95 The first mechanism is a sequential one, whereby the intermediate state becomes transiently populated in a scheme welldescribed by two-step kinetics. This mechanism dominates in energetic regimes satisfying E 1 > E 2 > E 3 .…”
Section: A Results For Population Dynamicsmentioning
confidence: 99%
“…In these experiments the primary electron donor (the special pair) is chemically oxidized, shutting down the electron transfer 43 so that only excited state energy transfer between the accessory bacteriochlorophyll (Bchl or B) and bacteriopheophytin (BPhy, or H) is possible. The 2D photon echo experiments by Lee et al 1 showed a long lived beating signal associated with |H B| coherent dynamics.…”
Section: Model Systemsmentioning
confidence: 99%
“…32 An alternative approach of comparable numerical intensity is given by a path integral formulation. 33,34 We present an alternative and numerically less intensive approach which uses perturbation theory for part of the exciton-vibrational coupling. It will be shown how the nonMarkovian effects for a whole manifold of low-frequency protein vibrations can be included in the theory.…”
Section: Introductionmentioning
confidence: 99%